TRAFFICKING IN WOMEN AND CHILDREN AS VULNERABLE GROUPS: TALKING THROUGH THEORIES OF INTERNATIONAL RELATIONS - Usman Mikail Usman (European Scientific Journal, ESJ, 2014)
Human trafficking is a global issue involving almost all countries. It is an issue that affects people of all ages, races, ethnicities, and gender throughout the world. This highly profitable trade poses a relatively low risk of capture or conviction when compared with trade in drugs and arms. The traffickers have a constantly regenerating commodity, the human body is very resilient in what it is able to withstand as far as pain and betrayal for the victims are concerned. Their targets are often children and young women, and their ploys are creative and ruthless, designed to trick, coerce and win the confidence of potential victims. This article will be analyzed from the perspective of International Relations theories, focusing particularly on feminist theory, absolutist theory, constructivist theory, conflict theory and trauma theory within the framework of international politics.